The Effect of Leadership Style and Motivation on Employee Performance with the Work Environment as a Moderating Variable (Universitas Negeri Semarang, 2022)
This study aimed (1) to determine and analyze the effect of leadership style on performance (2) to determine and analyze the effect of motivation on work performance (3) to determine and analyze the effect of leadership style on employee performance through the work environment (4) to determine and analyze the effect of motivation on performance through the work environment (5) to determine and analyze the effect of leadership style and motivation on employee performance. This study used quantitative methods. The data analysis technique used Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS). Based on the results of the study, it was concluded that leadership style had a positive and significant effect on employee performance. Motivation had a positive and insignificant effect on employee performance. Leadership style had a positive and significant effect on employee performance through the work environment. Motivation had a positive and insignificant effect on employee performance through the work environment. Leadership style and motivation had a positive and significant effect on employee performance.